Hubungan Dukungan Sosial dengan Keberfungsian Sosial pada Eks Pasien Covid-19 di Sulawesi Utara - Erika Emnina Sembiring; Lenny Gannika; Anggun Rizty Proklamasia Layuck (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
Covid-19 patients who have recovered often get stigma and discrimination from the surrounding community. The negative stigma given by the community affects the social functioning of former Covid-19 patients in the community. Social support from various parties such as family, friends, neighbors, co-workers is very much needed to improve the social functioning of former Covid-19 patients in the community. The purpose of this study was to determine the relationship between social support and social functioning in former Covid-19 patients in North Sulawesi. The research design used is descriptive correlation with a cross sectional approach, with a total sample of 164 respondents who were selected using the consecutive sampling method. The results of the study were analyzed using the Spearman test with a p value (0.000), this shows that there is a relationship between social support and social functioning in former Covid-19 patients. Good social support from family, friends, and the surrounding community allows former Covid-19 patients to carry out their social functions after recovering and returning to the community.